Oxford handbook of critical care nursing. - Baid, Heather; Creed, Fiona; Hargreaves, Jessica; Adam, Sheila K. ([Oxford] : Oxford University Press, 2016)
A practical, concise, easily accessible and evidence-based guide for all levels of nursing staff working in critical care environments.
Previous edition issued in print: published as by Sheila K. Adam and Sue Osborne. 2009.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on March 7, 2016).
Keywords: Intensive care nursing